2010
DOI: 10.1182/blood-2009-10-248245
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 acts as antitumor agent on childhood B-acute lymphoblastic leukemia cells

Abstract: Interleukin (IL)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…21,22 Purified FL/DLBCL cells from Pt #1 --6, #8 and #12 were co-cultured with murine fibroblast NIH-3T3 transfected with pIRES-neo bicystronic plasmid vector carrying the human CD40L gene (3T3/CD40L) (kindly provided by Dr Franco Fais, Department of Experimental Medicine, University of Genova). The same cells transfected with the empty vector (3T3/empty) were used as controls.…”
Section: Subjects and Methods Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Purified FL/DLBCL cells from Pt #1 --6, #8 and #12 were co-cultured with murine fibroblast NIH-3T3 transfected with pIRES-neo bicystronic plasmid vector carrying the human CD40L gene (3T3/CD40L) (kindly provided by Dr Franco Fais, Department of Experimental Medicine, University of Genova). The same cells transfected with the empty vector (3T3/empty) were used as controls.…”
Section: Subjects and Methods Patientsmentioning
confidence: 99%
“…19,20,27 Moreover, recent studies have shown that these cytokines can exert direct anti-tumor activity against solid and hematological malignancies. 17,21,22,28,29 Although the anti-tumor activity of IL-23 is quite controversial, 18,30,31 we 21 have demonstrated that IL-23 shows anti-leukemic effects by dampening directly pediatric B-acute lymphoblastic leukemia cell growth both in vitro and in vivo through the inhibition of cell proliferation and induction of apoptosis. In addition, we recently demonstrated that IL-27 acts as multifunctional anti-tumor agent in multiple myeloma (MM) 22 and inhibits acute lymphoblastic leukemia cell spreading in a pre-clinical model.…”
Section: Introductionmentioning
confidence: 97%
“…However, clinical trials with the anti-p40 antibody ustekinumab, which neutralizes both IL-23 and the related IL-12, have not been reproducibly effective in patients with Crohn disease (13,14). IL-23 also appears to promote tumor incidence and growth (15), but at least one report indicates that IL-23 has also anti-tumorigenic activity against pediatric B-acute lymphoblastic leukemia (B-ALL) cells (16), demonstrating (e.g. for Crohn disease and opposing roles in cancer development) that the biology of IL-23 is still incompletely understood.…”
Section: Signaling Of Interleukin 23 (Il-23) Via the Il-23 Receptor (mentioning
confidence: 99%
“…No information is available on IL-23 receptor expression and function in normal human B cells, with the only exceptions being plasma cells and early B lymphocytes (4,5). In this context, it has been shown that human plasma cells express complete IL-23 receptors and that IL-23 may modulate normal plasma cell functions (5).…”
Section: Interleukin-23mentioning
confidence: 99%
“…These cytokines are predominantly produced by antigen-presenting cells in response to microbial or host immune stimuli and are involved in the regulation of immune responses against infections and tumor development (2). Recent preclinical studies showed the direct antitumor activities of IL-12 family cytokines in different human hematologic malignancies, including pediatric acute leukemias and multiple myeloma, as well as in solid tumors (3)(4)(5)(6)(7). Here, we report and discuss recent advances in the role of IL-27 and IL-23 in multiple myeloma cells and their microenvironment and in human normal plasma cells.…”
Section: Introductionmentioning
confidence: 99%